2022
DOI: 10.35762/aer.2022.44.3.5
|View full text |Cite
|
Sign up to set email alerts
|

The Driving Force of Urban Water Body Change in Chonburi Province, Thailand

Abstract: The rapid urbanization from special economic zones (SEZs) in Asia poses a risk on water crisis. This paper identifies water body change trend and its driving force of change in Chonburi province; the most urbanized area in the Eastern Economic Corridor (EEC) of Thailand, in order to analyse the root cause of water shortage in the area. Land use maps from 2006 to 2019 were used to evaluate the changing trend in water bodies using land use transition matrix and land use dynamic degree. Panel data from 364 observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The rapid and intensive development forces this region into a context of considerable urban agglomeration, land use and land use changes (LULCC), and environmental degradation (Boonyanam & Bejranonda, 2022; Diep et al, 2022; Mekparyup & Saithanu, 2020; Thongphunchung et al, 2022). The region has seen a more prominent urbanization in coastal areas during 2007–2016, and this trend will continue in the future at a rate of 2.40% per year (Tontisirin & Anantsuksomsri, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid and intensive development forces this region into a context of considerable urban agglomeration, land use and land use changes (LULCC), and environmental degradation (Boonyanam & Bejranonda, 2022; Diep et al, 2022; Mekparyup & Saithanu, 2020; Thongphunchung et al, 2022). The region has seen a more prominent urbanization in coastal areas during 2007–2016, and this trend will continue in the future at a rate of 2.40% per year (Tontisirin & Anantsuksomsri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A healthy and diverse ecological environment is crucial for regional development to address environmental challenges, promote sustainability, and ensure human well‐being. Previous studies indicated that the natural ecosystems (i.e., paddy fields, horticulture, and forest) in the EEC have experienced a reduction in both area and economic values (Boonyanam & Bejranonda, 2021, 2022; Tontisirin & Anantsuksomsri, 2021). If this trend continues in the future, it will be challenging to balance the tradeoffs between urban‐industrial agglomeration and nature losses, especially under a high demand on land budget, increasingly intensive production, high water demand, and severity of drought and climate change (Mon et al, 2022; Nitivattananon & Srinonil, 2019; Promping & Tingsanchali, 2021; Samanmit et al, 2022; Wongsa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%